WirelyMoody / Nik Anis Aziera … [et al.] - Nik Anis Aziera, Nik Anis Aziera; Nur Amira, Nur Amira; Eyaminah, Eyaminah; Anisa Zurani, Anisa Zurani; Amira Nurfarhanis, Amira Nurfarhanis; Muhammad Fairuz, Muhammad Fairuz (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
WirelyMoody is a multifunctional device that gives the user joy. This device is an innovation from wifi to a four-in-one product that includes a pendrive, powerbank, and MP3 player. This product is advantageous to the user since it reduces the user's weight, space, and time requirements. The primary goal of this product is to create an innovative high-end technological gadget with versatile capabilities. Carryable gadget helps consumers save room in their bags. The majority of individuals carry multiple devices in their bags, which may become inconvenient and hefty. People listen to music, charge their phones and other gadgets, and access the internet via a variety of devices. The product's focus is on a solution that is compatible. This solution is appropriate for someone who has a space constraint. There's no such thing as a one-size-fits-all bag. One gadget, such as WirelyMoody, can solve the problem as a four-in-one device. With a fair price of RM170, this innovative product will generate a significant profit margin and become a popular item in 2022-2023, meeting the needs of a wide range of consumers.